PENGARUH TABATA TRAINING DAN HIGH INTENSITY INTERVAL TRAINING TERHADAP PENINGKATAN KEKUATAN OTOT TUNGKAI - Cemara, Rizky Aris; Fauqi, Amal (Jurnal Ilmiah Mandala Education (JIME), 2022)
This study used a "randomized group pretest and posttest design". The population in this study were male students of the PJKR STKIP Yapis Dompu Study Program class of 2021, totaling 100 people. The sampling technique used random sampling with a sample of 30 people, divided into 3 groups, namely the Tabata Training group, High Intensity Interval Training and the last group, the control group. This type of research is a quasi-experimental, with a quantitative approach. Data were collected by measuring technique using a back and leg dynamometer to measure leg muscle strength. Data were analyzed using MANOVA technique, using 0.05. Based on the results of this study indicate that the effect of tabata training on increasing strength with a value of p = 0.000, then the effect of high intensity interval training on increasing strength with a value of p = 0.000. From the two exercises, it turned out that high intensity interval training was better than tabata training in increasing leg muscle strength.